ICT AND VOCABULARY BUILDING - Bastian Sugandi; Eko Saputra (Bandar Lampung University (UBL), 2016)
The use of ICT (Information and Communication Technologies) in teaching English language is very useful. The availability of various applications makes teaching and learning more effective. There are Vocabulary Builder, Test Your English Vocabulary, English Vocabulary, English Vocabulary Daily, Antonyms and Synonyms Vocabulary, Vocabulary, 10000Q English Vocabulary Test, and TOEFL Vocabulary Flashcard. These kinds of applications can help teachers in teaching English.